Creating a Sport and Exercise Medicine Masters syllabus for doctors: a Delphi study. Issue 2 (8th April 2022) - Vishnubala, Dane; Iqbal, Adil; Marino, Katherine Rose; Salman, David; Pringle, Andy; Nykjaer, Camilla; Bazira, Peter; Finn, Gabrielle
Abstract : Objective: Sport and Exercise Medicine (SEM) Masters curricula vary. This Delphi study is aimed to create a consensus curriculum for doctors undertaking SEM Masters courses. Methods: A modified Delphi survey was used. An expert panel was established of individuals deemed to have adequate knowledge of the field. The research group developed the initial draft of the curriculum by collating and reviewing previously published UK-based postgraduate SEM-related curricula. There were two phases. In phase 1 the expert group either accepted, rejected or modified each learning objective (LO). During phase 2 the expert group were asked to accept or reject each LO that did not get accepted outright previously. The research group analysed the levels of agreements and the comments given by the expert panel after each phase. Results: The expert panel consisted of 45 individuals, with 35 completing phase 2 (78% retention rate). Of the 136 LOs initially collated: 71 (52%) were accepted outright, 60 (44%) were altered in some way and reincluded in phase 2, and 5 (4%) were removed after phase 1. The research group added 2 (1%) new LOs on reflection over comments made by the expert panel. The final curriculum contained 133 LOs, divided into 11 subthemes. Conclusions: The findings will better inform educators when developing SEM Masters curricula and inform students what they should look for when considering an SEM Masters. This consensus curriculum is an important step in standardising postgraduate SEM education.